THE EFFECT OF INHIBITION OF LNCRNA MIR100HG ON THE PROLIFERATION OF HUMAN PROMYELOCYTIC LEUKEMIA CELLS: Life Science-Histology - BAGHERI, MARZIEH; SHARIFI, MOHAMMADREZA; SALEHI, MAHSA (International Journal of Life Science and Pharma Research, 2019)
lncRNAs are one of the main classes of non-coding RNAs, responsible for RNA regulation in a variety of cellular processes, and their effect on human cancer remains largely unexplored; Abnormal expression of lncRNAs has been shown to be associated with many human diseases and cancers, such as leukemia. Acute promyelocytic leukemia (APL) is the M3 subtype of acute myeloid leukemia (AML), with the aberrant accumulation of promyelocytes. One of the lncRNAs that showed upregulation in AML is lncRNA MIR100HG, involved in different cancers. The aim of our study is to investigate the functional role of MIR100HG antisense LNA GapmeRs, on APL cells. In this experimental study, we have used an Antisense LNA GapmeRs, in order to block MIR100HG in APL Cells. HL60 (APL cell line) cells were transfected with MIR100HG antisense LNA GapmeRs and at three different time points (24, 48 and 72 h) and were investigated apoptosis, necrosis, MIR100HG and TGFβ expression. MIR100HG inhibition could reduce the viability of HL- 60 cells, through induction of apoptosis; because of the TGFβ upregulation. qRT-PCR was performed to determine the MIR100HG expression by antisense LNA GapmeRs. Our results suggest that degradation of MIR100HG could serve as a novel approach for controlling the proliferation of APL cells and therefore, can be used in translational medicine for targeted therapy in APL